Parallel Computing and Education. - Fox, Geoffrey C. (Daedalus: Journal of the American Academy of Arts & Sciences)
Describes how parallel computing will dramatically affect education by changing the way children are taught and what is taught. Suggestion that parallel architectures will lead to computers of greater performance and capability; Statement that current curricula at grade schools and colleges will not educate students to exploit the possibilities opened up by parallel computers and computational methodology; Need for skilled people to explore and exploit these possibilities; More.